2013
DOI: 10.1002/lary.24204
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing kinematics and airway protection after palatal local anesthesia in infant pigs

Abstract: Objective Abnormal kinematics during swallowing can result in aspiration which may become life threatening. We tested the role of palatal sensation in the motor control of pharyngeal swallow in infants. Study Design In eight infant pigs, we reduced palatal sensation using local anesthesia (PLA) and measured the impact on swallowing kinematics and airway protection. Methods The pigs drank milk containing barium while we simultaneously recorded videofluoroscopy and electromyography from fine wire bipolar ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 29 publications
(51 reference statements)
1
16
0
Order By: Relevance
“…Infant pigs have been used in previous studies of normal feeding and swallowing neurophysiology, and thus a large body of comparable data exists for comparison with the results of this study [4, 12, 17, 21, 22]. The data used here were collected as control data in other studies of dysphagia [8, 9, 23, 24]. The methods used are described in detail in those articles and briefly reviewed here.…”
Section: Methodsmentioning
confidence: 99%
“…Infant pigs have been used in previous studies of normal feeding and swallowing neurophysiology, and thus a large body of comparable data exists for comparison with the results of this study [4, 12, 17, 21, 22]. The data used here were collected as control data in other studies of dysphagia [8, 9, 23, 24]. The methods used are described in detail in those articles and briefly reviewed here.…”
Section: Methodsmentioning
confidence: 99%
“…Surgical or pharmacological models of stroke in rodents have been common, but are now being developed and validated for examining dysphagia [19, 44]. Injuries that are associated with dysphagia, such as damage to branches of the vagus nerve, recurrent or superior laryngeal nerve [11, 12, 16, 38], or other sensory deficits [18], can be relatively easily duplicated in animal models.…”
Section: Ceteris Paribus and Understanding Pathophysiologymentioning
confidence: 99%
“…However, recent work has indicated that airway protection deficits following RLN lesion are associated with changes in the timing and extent of tongue movements during intraoral transport and the swallow [7]. In addition, both anesthesia [8] and stimulation [9] of oral sensory pathways change swallow parameters and airway protection outcomes, highlighting the importance of sensory modulation of the swallow by structures throughout the oral, pharyngeal, and laryngeal complex. This suggests that the biomechanics of transport of the liquid bolus from the valleculae to the pharynx may be modified in infants with a recurrent laryngeal nerve lesion.…”
Section: Introductionmentioning
confidence: 99%
“…We use our validated infant pig model [8,11,12] in order to do controlled nerve injuries and collect amounts of data impossible in vulnerable infant clinical populations. Infant pigs are a good model for infant humans through similar size [13], similar anatomy (a fleshy, muscular tongue, muscular cheeks and an intranarial larynx) and a similar mode of drinking (tongue based suction rather than lapping) [14].…”
Section: Introductionmentioning
confidence: 99%